2004
DOI: 10.1186/cc2978
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Rhabdomyolysis ranges from an asymptomatic illness with elevation in the creatine kinase level to a life-threatening condition associated with extreme elevations in creatine kinase, electrolyte imbalances, acute renal failure and disseminated intravascular coagulation. Muscular trauma is the most common cause of rhabdomyolysis. Less common causes include muscle enzyme deficiencies, electrolyte abnormalities, infectious causes, drugs, toxins and endocrinopathies. Weakness, myalgia and tea-colored urine are the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
343
0
13

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 708 publications
(362 citation statements)
references
References 124 publications
6
343
0
13
Order By: Relevance
“…The clinical spectrum ranges from asymptomatic elevation of serum creatine kinase concentration to acute kidney injury (AKI) and multiorgan failure. Major causes of rhabdomyolysis include trauma, exertion, hypoxia, infections, metabolic disorders, drug toxicity and other [1,2,3]. …”
Section: Introductionmentioning
confidence: 99%
“…The clinical spectrum ranges from asymptomatic elevation of serum creatine kinase concentration to acute kidney injury (AKI) and multiorgan failure. Major causes of rhabdomyolysis include trauma, exertion, hypoxia, infections, metabolic disorders, drug toxicity and other [1,2,3]. …”
Section: Introductionmentioning
confidence: 99%
“…Physical etiologies include trauma, arterial occlusion, overexertion, seizures, delirium tremens, electrical injury, and hyperthermia. Nonphysical triggers include metabolic syndromes, toxins/drugs, infections, electrolyte abnormalities, endocrinopathies, and autoimmune conditions 3. His history did not reveal any physical triggers.…”
Section: Discussionmentioning
confidence: 99%
“…[2] Common causes of rhabdomyolysis include extreme physical exertion, extensive tissue injury, metabolic derangements, drugs, and toxins. [1][2][3] Interestingly, few case reports have suggested that some dietary weight loss supplements could predispose to rhabdomyolysis. [4][5][6] It is theorized that ingredients in these products are directly toxic to myocytes and also impair intracellular calcium homeostasis leading to myonecrosis, especially in the setting of concomitant exertion.…”
Section: Introductionmentioning
confidence: 99%